Understanding Science in Conservation: A Q Method Approach on the Galápagos Islands - Rose C Cairns (Conservation & Society, 2012)
The variety of perspectives that conservation practitioners and scientists from different disciplinary backgrounds have towards the role of science in conservation add to the already complex nature of most contemporary conservation challenges, and may result in conflict and misunderstanding. This study used Q method (a form of discourse analysis with roots in psychology) in order to uncover the range of perspectives on the science/conservation interface currently held by scientists and conservation managers working on the Galαpagos Islands. The aim was to facilitate mutual understanding and communication between proponents of the various viewpoints, as well as to expose the subjective values, assumptions, and interests on which these opinions are constructed, to critical scrutiny. Twenty-seven people from a range of disciplinary and professional backgrounds carried out a Q test consisting of a sample of 34 selected opinion statements. Four statistically different perspectives emerged from the analysis, emphasising different concerns and highlighting different understandings of science and conservation. The perspectives have been labelled as: 1) Science for management; 2) Freedom of science; 3) Limits of science; and 4. Separation of science and conservation. The similarities and differences between the perspectives are discussed in depth, and the implications for conservation practice are explored in light of the current literature.